Salubrinal Protects Against Cisplatin-Induced Cochlear Hair Cell Endoplasmic Reticulum Stress by Regulating Eukaryotic Translation Initiation Factor 2α Signalling - Lu, Wen; Ni, Kun; Li, Zhuangzhuang; Xiao, Lili; Li, Yini; Jiang, Yumeng; Zhang, Jincheng; Shi, Haibo (Frontiers in Molecular Neuroscience, 2022)
Objective Cisplatin is a broad-spectrum anti-tumour drug commonly used in clinical practice. However, its ototoxicity greatly limits its clinical application, and no effective method is available to prevent this effect. Endoplasmic reticulum stress (ERS) is reportedly involved in cisplatin ototoxicity, but the exact mechanism remains unclear. Therefore, this study aimed to investigate the role of eukaryotic translation initiation factor 2α (eIF2α) signalling and its dephosphorylation inhibitor salubrinal in cisplatin ototoxicity. Methods We evaluated whether salubrinal could protect against cisplatin-induced damage in House Ear Institute-Organ of Corti 1 (HEI-OC1) cells and mouse cochlear explants. By knocking down eIF2α, we elucidated the vital role of eIF2α in cisplatin-induced damage in HEI-OC1 cells. Whole-mount immunofluorescent staining and confocal microscopy of mouse cochlear explants and HEI-OC1 cells were performed to analyse cisplatin-induced damage in cochlear hair cells and the auditory cell line. Results Data suggested salubrinal attenuated cisplatin-induced hair cell injury by inhibiting apoptosis. In addition, salubrinal significantly reduced ERS levels in hair cells via eIF2α signalling, while eIF2α knockdown inhibited the protective effect of salubrinal. Significance Salubrinal and eIF2α signalling play a role in protecting against cisplatin-induced ototoxicity, and pharmacological inhibition of eIF2α-mediated ERS is a potential treatment for cisplatin-induced damage in the cochlea and HEI-OC1 cells.